Excel-Based Accounting Practices in Village-Owned Enterprises (BUMDes): Enhancing Transparency of Food Security Program Funds - Sugiartono, Endro; Ahmad, Arisona; Hartanto, Sugeng; Wiyono, Luluk Cahyo; Nahrudi, Nahrudi (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
Village-Owned Enterprises (BUMDes) have a strategic role in managing food security funds sourced from the Village Fund, particularly in supporting agricultural inputs, local farming, and community food resilience programs. Despite this potential, financial management in many BUMDes remains manual, making it vulnerable to errors and a lack of transparency. This study investigates how the use of Excel-based accounting, as a simple and low-cost digital tool, enhances the accountability of BUMDes in managing food security program funds. The research employs a qualitative case study design focused on BUMDes Mandiri in Suci Village, Panti Subdistrict, Jember Regency. Data were collected through in-depth interviews with BUMDes managers, review of financial documents, and field observations. The findings indicate that Excel-based accounting improves the standardization of financial records and increases transparency by producing reports that stakeholders, including village officials and local communities, can more easily understand. However, challenges remain, particularly limited human resources and insufficient skills in operating advanced Excel functions. This study contributes to the literature on public sector accounting by highlighting the role of simple digital solutions in strengthening accountability at the village level. Practically, the results emphasize the importance of capacity building and digital literacy programs to support sustainable financial governance in BUMDes. Moreover, the study provides policy implications for enhancing the governance of Village Fund in alignment with Sustainable Development Goals (SDG 2: Zero Hunger and SDG 8: Decent Work and Economic Growth).